An overview of nitrogen‐doped MXenes and their recent developments - Dongsheng Li; Xu Zheng; Philippe Boutinaud; Yihua Hu; Sanshui Xiao; Jie Xu; Chuanlong Wang; Yidong Hou; Zhiyu He; Wei Huang; Fengwen Kang (Responsive Materials, 2024)
Abstract MXenes and their derivatives have attracted tremendous attention over the past few decades, and several reviews have already been dedicated to their synthesis, properties, device functionalities, and performances. Nitrogen (i.e., N), as an important non‐metal element, has been widely reported as an external dopant to improve the properties of MXenes. Herein, we review the recent advances of N‐MXenes, with a significant concern on the impact of N‐doping on the structural and photo‐/electrochemical properties of bulk MXenes, and their emerging applications. The different types of recently reported N‐MXenes and the associations between the N‐doping and the structural characteristics (e.g., the change of atomic lattice and the number and type of active sites, as well as the removal of detrimental functional groups) of MXenes are systematically summarized and discussed, with the aim to highlight the resulting improvements in response to the photo‐/electrochemical and electronic stimuli. Applications of the N‐MXenes in the fields of electrochemistry, photo‐/electrocatalysis, and photosensing are then described. Finally, we summarize this review, and disclose our perspectives on the future opportunities of the N‐MXenes and the potential development challenges of this research branch.